Modelling wave–structure interactions including air compressibility: A case study of breaking wave impacts on a vertical wall along the Saint-Lawrence Bay. (1st April 2023) - Croquer, Sergio; Díaz-Carrasco, Pilar; Tamimi, Vahid; Poncet, Sébastien; Lacey, Jay; Nistor, Ioan
Abstract: Climate change and the associated rise in sea levels impose a challenge for current methods used to predict the processes involved in wave–coastal structure interactions: stochastic nature, coexistence of various phenomena with very different time and length scales, wave transformations ... The main objective of this study is to extend the range of numerical tools available to coastal engineers by presenting a two-phase Favre-Averaged Navier–Stokes model to study wave dynamic interactions with impermeable structures. The model takes into account air compressibility as well as turbulence effects. The model is first validated with two experimental test cases: a sloshing tank with impacts, and wave impacts on a vertical wall with an overhanging slab. After validation, the model is confidently used for the analysis of wave interactions with vertical walls along the Saint-Lawrence Bay, Quebec, Canada. Four incident wave cases representing frequent and extreme storm conditions are selected using the statistical data of a buoy. Results are discussed primarily in terms of the hydrodynamic loads and overtopping on the structure for two breaking and two non-breaking wave cases. Highlights: An OpenFOAM solver for wave impacts including air compressibility effects was built. Breaking waves dynamics and interactions with impermeable structures are captured. A scenario with realistic wave conditions and bathymetry has been simulated. Incident wave data from a buoy located in situ has been used for simulation. Forces and overtopping by breaking and non-breaking waves on the wall are presented.